Implementasi Teknologi Microbubble Generator pada Pengolahan Limbah Cair Kotoran Sapi - Lathifa Putri Afisna; Muhammad Syaukani; Ilham Dwi Arirohman; Harmiansyah Harmiansyah; Devia Gahana Cindi Alfian (CV. Multi Kreasi Media, 2022)
Along with the development of the cattle farming industry in Indonesia, many problems arise in terms of waste management. Cow dung waste processing becomes a challenge for the cattle farm industries, especially in handling the liquid waste. Liquid waste produced by cattle farming may pose a negative impact on the health of the people living around the cattle farm if it is not managed properly. One of the efforts to reduce environmental damage due to liquid waste from the farm is by utilizing microbubble generator (MBG) technology to decompose cow dung liquid waste into environmentally friendly waste. The aeration process that occurs in cow dung liquid waste helps aerobic microorganisms to better decompose liquid waste through the addition of dissolved oxygen produced by the microbubble generator in the water. As one of our community service programs, our team came up with an initiative to transfer the know-how of the MBG-based wastewater processing system to a local cattle farm, CV Sanjaya Farm. The program implementation method is by providing training and assistance in the application of MBG technology in the processing of cow dung liquid waste. With an active participation of both our team and partner sides, the MBG technology has been installed at our partner’s locations. As a result of the training and mentoring that we delivered at the partner farm, we observed an increase in the knowledge and skills of both leadership and staff of the partner farm in overcoming the problem of liquid waste management. In addition, a tangible solution has also been built for handling liquid waste to be disposed of into the surrounding environment in a safe and non-polluting manner.